PENGARUH KAIZEN COSTING DAN KEUNGGULAN KOMPETITIF TERHADAP KEBERLANJUTAN UMKM - Montana, Louisa Anastasia; Animah, Animah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
MSMEs are businesses that play a role in supporting economic growth in Indonesia. A business is said to considered successful if it is able to achieve sustainability. Some factors that are considered to affect business sustainability are the application of kaizen costing and competitive advantage. The purpose of this study was to examine kaizen costing and competitive advantage affect sustainability. 72 respondents made up the overall sample size for this study, which was carried out at the Geprek Chicken MSMEs in Mataram City. This study uses primary data by distributing questionnaires as a data collection method and is distributed through the use of google form. This research uses SPPS Version 18 as an analysis tool and multiple linear regression as a data analysis technique. The research findings reveal that kaizen costing has no effect on the sustainability of MSMEs. While competitive advantage affects sustainability in MSMEs. The implication of this study is that kaizen costing, as an approach that emphasises continuous improvement in operational processes, can produce efficiencies that can contribute positively to sustainability. Similarly, competitive advantage can act as a key driver in long-term and sustainable growth.